Critical storytelling during the COVID-19 pandemic : Berea College students share their experiences - Hartlep, Nicholas Daniel; Stuchell, Christopher V.; Whitt, Nathaniel Elisha; Hensley, Brandon O. (Emerald Publishing Limited : Information Age Publishing, Inc, 2021)
Personal writings about the COVID-19 pandemic by students enrolled in spring 2020 education courses (EDS 150A and EDA 150B) at Berea College.
Minimal Level Cataloging Plus.
Keywords: Berea College -- Students.; COVID-19 (Disease) -- Social aspects.; elektronické knihy; Personal narratives; Poetry; Creative nonfiction; Education -- General.; Fiction: Traditional stories, myths and fairy tales.; Education.; electronic books